The Implementation of Infant Anoesis and Adult Autonoesis in the Retrogenesis and Staging System of the Neurocognitive Disorders: A Proposal for a Multidimensional Person-Centered Model - Alessandro Pirani (Geriatrics)
Background: Retrogenesis is the process by which the degenerative and vascular mechanisms of dementia reverse the order of acquisition in the normal development. Objective: The development of memory/knowledge after birth may help to know the biopsychosocial and functional characteristics (biosphere) of the retrogenesis. Methods: A literature review was performed in the PubMed, Google Scholar, and Scopus databases using 43 keywords related to retrogenesis: 234 eligible records were selected. Results: The infantile amnesia, characterized from anoesis, was described along the infant/child’s biosphere in which the limbic system progressively develops the acquisition of the body knowledge (Anoetic Body Consciousness, AnBC). Anoesis is the infant memory state characterized by the absence of long-term memories of the many stressful/painful experiences that accompany the acquisition under the long-life voluntary control of the long-term memories fundamental for the body growth and survival (mainly chewing/swallowing and walking). At the age of 3–4 years, usually, the AnBC evolves, as a continuum, into the adulthood autonoesis with the emergence, in the child/adolescent, of the consciousness of “self” trough the development of the Episodic Autobiographic Memory (EAM) and the Autonoetic Mind Consciousness (AuMC). The development of cognition and knowledge is due to the progressive maturation of the whole limbic system and not only of the hippocampus. In the biopsychosocial retrogenesis, the EAM/AuMC vanishes progressively along the mild, moderate, and severe stages of dementia when the infant AnBC resurfaces, losing progressively the basic activities of daily living in a retrogenetic order of acquisition where the last functions to disappear are chewing/swallowing. Conclusion: The transition from the adult EAM-AuMC to the infant AnBC, as a continuum in the individual biosphere, adds a contribution to the assessment of the retrogenesis in dementia from a multidimensional person-centered model.